KOMUNIKASI YANG BAIK UNTUK MOTIVASI BELAJAR TERHADAP HASIL BELAJAR - Fransisca Tassia (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The phenomenon found in the research that the students achievement in TIK at SMAN 16 Padang were under the Minimum Achievement Criteria (KKM).The purposes of the research are to find out (1) the influence of inquiry method to TIK achievement, (2) the influence of using inquiry method in high motivation students to the students achievement at SMAN 16 Padang. This research was an experiment research, the research was designed in difference model, the research used inquiry method in TIK subject. The research design was treatment by block 2X2. The population and the sample of the research were two classes at class XI. The data collection instrument by using several instrumentation, there were the instrumentation for students achievements and the instrumentation for students' learning motivation by using test of validation, reliability, level of distinction and level of difficulty. The technique of analyzing the data was descriptive data, significance test and hypothesis test. The Findings of the research found that the students learning by using inquiry method got higher score in TIK than the students learning by using conventional method, the high motivation students in learning through inquiry method in TIK got higher score than the students learning by using conventional method. From the findings the researcher concluded that (1) There were differences between the result of students achievements by using inquiry method in TIK and students achievements by using conventional method. (2) There were differences between the result of high motivation students achievements learning through inquiry method and learning by using conventional method. (3) There were differences between the result of low motivation students achievements learning through inquiry method and learning by using conventional method. (4) There is no interaction of using inquiry method and students motivation to the students TIK achievement at SMAN 16 Padang. As a result, In this research Inquiry method and learning motivation could improve students TIK